Eat, sleep, innovate : how to make creativity an everyday habit inside your organization - Anthony, Scott D. (Harvard Business Review Press, 2020)
"From the author of The Little Black Book of Innovation, a new guide for using the power of habit to build a culture of innovation. Leaders have experimented with open innovation programs, corporate accelerators, venture capital arms, skunkworks, and innovation contests. They've trekked to Silicon Valley, Shenzhen, and Tel Aviv to learn from today's hottest, most successful tech companies. Yet most would admit they've failed to create truly innovative cultures. There's a better way--and it all starts with the power of habit. In Eat, Sleep, Innovate, innovation expert Scott Anthony and his impressive team of coauthors use groundbreaking research in behavioral science to provide a first-of-its-kind playbook for empowering individuals and teams to be their most curious and creative--every single day. Throughout the book, the authors reveal dozens of hacks and habits they've collected from workplaces across the globe that will unleash the natural innovator inside everyone. In addition to case studies of "normal organizations doing extraordinary things," they provide readers with the tools to create their own hacks and habits, which they can then use to build and sustain their own models of a culture of innovation. Fun, lively, and utterly unique, Eat, Sleep, Innovate is the book you need to make innovation a natural and habitual act within your team or organization"--